Plasticity in brain activity dynamics after task-shifting training in older adults. (January 2020) - Dörrenbächer, Sandra; Wu, Carolyn; Zimmer, Hubert; Kray, Jutta
Abstract: Cognitive control is supported by a dynamic interplay of transient (i.e., trial-related) brain activation across fronto-parietal networks and sustained (i.e., block-related) activation across fronto-striatal networks. Older adults show disturbances in this dynamic functional recruitment. There is evidence suggesting that cognitive-control training may enable older adults to redistribute their brain activation across cortical and subcortical networks, which in turn can limit behavioral impairments. However, previous studies have only focused on spatial rather than on temporal aspects of changes in brain activation. In the present study, we examined training-related functional plasticity in old age by applying a hybrid fMRI design that sensitively tracks the spatio-temporal interactions underlying brain-activation changes. Fifty healthy seniors were assigned to a task-shifting training or an active-control group and their pretest/posttest activation-change maps were compared against 25 untrained younger adults. After training, older adults showed the same performance as untrained young adults. Compared to the control group, task-shifting training promoted proactive (i.e., early, cue-related) changes in transient mechanisms supporting the maintenance and top-down biasing of task-set representations in a specific prefrontal circuitry; reactive (i.e., late, probe-related) changes in transient mechanisms supporting response-selection processes in dissociable fronto-parietal networks; overall reductions of sustained activation in striatal circuits. Results highlight the importance of spatio-temporal interactions in training-induced neural changes in age. Highlights: Investigation of neural changes after task-shifting training in old age. Methodically applying an hybrid fMRI design to capture brain activity dynamics. Training promoted changes in transient mechanisms in fronto-parietal networks. Training promoted overall reductions of sustained activation in striatal circuits. Spatio-temporal interactions may underlie training-related brain activity changes.